Influencial factors of domestic tourists‘ intention to choose wellness-tourism destinations in Vietnam - Vu, Huong Giang; Tran, Thu Phuong; Luong, Thanh Thao (Jurnal Pariwisata Nusantara (JUWITA), 2024)
Purpose: Determine the impact of influencial factors on the intention to choose wellness tourism destination in Vietnam of domestic tourists. Method: The research used mixed methods which include quantity and quality methods. Desk research was firstly used to synthesize research background and develop research model. After that, a survey was implemented to collect data to test the hypothesis. Finally, focus group discussion was used to collect opinions of policy makers, tourism specialists on solutions to enhance domestic tourists’ intention to choose wellness tourism destination in Vietnam. Result: The result of the study shows that there are 4 factors affects the intention of domestic tourists’ in choosing wellness tourism destination in Vietnam: Attitude, subjective norms, perceived behavioral control and destination image. In which perceived behavioral control has the strongest impact and destination image is the only factor that has negative impact. Some solutions have been proposed to to optimize the impact factors, contributing to the promotion of sustainable development of wellness tourism in Vietnam. Contribution: The study makes contribution to clarifying the factors influencing domestic tourists' intention to choose wellness-tourism destinations in Vietnam which are attitude, subjective norms, perceived behavioral control and destination image. Based on the analysis results, some practical solutions to enhance domestic tourists' intention to choose wellness tourism destination in Vietnam were proposed: raising awareness of behavioral control by providing detailed information, developing flexible service packages, and improving infrastructure so that tourists feel autonomous and comfortable when deciding; enhancing subjective norms by encouraging sharing of travel experiences on social networks, cooperating with KOLs, and organizing group travel programs to take advantage of community influence; improving tourists' attitudes by diversifying and improving the quality of tourism products, building a positive environment at the destination, and promoting the benefits of wellness tourism; and improving the destination's image through strong communication campaigns, developing unique experience programs, and cooperating with international organizations to certify quality, create prestige, and attract tourists.